We know
in the graph two points
point 1 (2,1) and point 2 (-1,-4)
the equation in point-slope form is ----------------> (y-y1)=m(x-x1)
step 1
find the value of m
m=(y2-y1)/(x2-x1)----------> (-4-1)/(-1-2)--------> m=5/3
step 2
with the point (-1,-4) and m=5/3
find the equation in point-slope form
(y-(-4))=(5/3)*(x-(-1))-------------> (y+4)=(5/3)(x+1)
the answer is the option d) ( y+ 4 ) =+ 5/3 ( x + 1 )
E^(xy) = 2
(xdy/dx + y)e^(xy) = 0
At point (1, ln2), dy/dx + ln2 = 0
dy/dx = -ln2
Upload a pic so we can help
Answer:
366127232
Step-by-step explanation:
i just divided the number and exponent and assumed x equals to 1 cause every variable is =to 1 unless it tells you what it equals to.
Answer:
y+3 = -6(x+9)
Step-by-step explanation:
m(x-x1)= (y-y1)
-6[x-(-9)] = [y-(-3)]
-6(x+9) = y+3
.....